Robust Design Optimization of Electrical Machines and Devices - Orosz, Tamás; Pánek, David; Rassõlkin, Anton; Kuczmann, Miklos (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains fourteen chosen articles on robust design optimization of electrical machines and devices. Optimization is essential for the research and design of electromechanical devices, especially electrical machines. Finding optimal solutions may lead to cheaper and more efficient production of electrical machines. However, optimizing such a complex system as an electrical machine is a computationally expensive optimization problem, where many physical domains should be considered together. However, a good, practical design should be insensitive to parameter changes and the manufacturing tolerances. The collected papers show how modern artificial intelligence (AI) tools can be used for the robust design optimization of electric machines and electrical devices. The articles which are published in this Special Issue present the latest results of current research fields. Hopefully, the presented models and various application fields will provide useful information for researchers and professionals interested in these techniques themselves or who have other problems from different fields.